Effect of crosslinking in cartilage-like collagen microstructures. (February 2017) - Chen, Ying-chun; Chen, Minsi; Gaffney, Eamonn A.; Brown, Cameron P.
Abstract: The mechanical performance of biological tissues is underpinned by a complex and finely balanced structure. Central to this is collagen, the most abundant protein in our bodies, which plays a dominant role in the functioning of tissues, and also in disease. Based on the collagen meshwork of articular cartilage, we have developed a bottom-up spring-node model of collagen and examined the effect of fibril connectivity, implemented by crosslinking, on mechanical behaviour. Although changing individual crosslink stiffness within an order of magnitude had no significant effect on modelling predictions, the density of crosslinks in a meshwork had a substantial impact on its behaviour. Highly crosslinked meshworks maintained a 'normal' configuration under loading, with stronger resistance to deformation and improved recovery relative to sparsely crosslinked meshwork. Stress on individual fibrils, however, was higher in highly crosslinked meshworks. Meshworks with low numbers of crosslinks reconfigured to disease-like states upon deformation and recovery. The importance of collagen interconnectivity may provide insight into the role of ultrastructure and its mechanics in the initiation, and early stages, of diseases such as osteoarthritis. Abstract : Highlights: Highly interacting fibre networks maintain a 'normal' configuration with loading. Networks with sparse interactions revert to a 'diseased' configuration. Maintenance of structural integrity is at the expense of high stresses in fibres. The density of interaction sites had more influence than their properties.